2012
DOI: 10.1029/2011gl050722
|View full text |Cite
|
Sign up to set email alerts
|

Holocene aridification of India

Abstract: Spanning a latitudinal range typical for deserts, the Indian peninsula is fertile instead and sustains over a billion people through monsoonal rains. Despite the strong link between climate and society, our knowledge of the long‐term monsoon variability is incomplete over the Indian subcontinent. Here we reconstruct the Holocene paleoclimate in the core monsoon zone (CMZ) of the Indian peninsula using a sediment core recovered offshore from the mouth of Godavari River. Carbon isotopes of sedimentary leaf waxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
200
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 223 publications
(219 citation statements)
references
References 40 publications
19
200
0
Order By: Relevance
“…The NGHP-01-19B core location is nearest to the Mahanadi River, but may also be influenced by the discharges of other CMZ rivers (Phillips et al, 2014a), thus the variations in the ecological assemblages observed in our study should reflect Indian monsoon variability and magnitude. Lithostratigraphic characteristics indicate that mass transfer events played no role in sedimentation at our sites for the periods considered in our study (Collet et al, 2008;Ponton et al, 2012;Phillips et al, 2014b).…”
Section: Marine Coresmentioning
confidence: 72%
See 4 more Smart Citations
“…The NGHP-01-19B core location is nearest to the Mahanadi River, but may also be influenced by the discharges of other CMZ rivers (Phillips et al, 2014a), thus the variations in the ecological assemblages observed in our study should reflect Indian monsoon variability and magnitude. Lithostratigraphic characteristics indicate that mass transfer events played no role in sedimentation at our sites for the periods considered in our study (Collet et al, 2008;Ponton et al, 2012;Phillips et al, 2014b).…”
Section: Marine Coresmentioning
confidence: 72%
“…The portion of core NGHP-01-16A (16°35.59'N / 082°41.00'E, 1265 m water depth, 217 m total length) sampled in this study (0-875 cm) covers the entire Holocene until HS 2. The sediments are composed of smectite-dominated hemipelagic clays commonly bearing calcareous nannofossils, foraminifera, and silt/sand lamina/beds (Phillips et al, 2014a) and terrestrial dominated organic carbon (Johnson et al, 2014) originating from the Godavari River during the last 27,000 years cal BP (Ponton et al, 2012). We also studied samples from core NGHP-01-19B (18°58.66'N / 85°39.52'E, 1,433m water depth, 26 m total length) that was collected close to the Mahanadi River outlet.…”
Section: Marine Coresmentioning
confidence: 99%
See 3 more Smart Citations